PENAMBAHAN EKSTRAK KEPALA UDANG GALAH (Macrobrachium rosenbergii de man) UNTUK MENINGKATKAN KANDUNGAN PROTEIN PADA PRODUK OLAHAN STICK - Rabiatul Adawyah Adawyah; Siti Aisyah; Findya Puspitasari; Candra Candra (Fish Scientiae, 2019)
This research aims to obtain an exact comparison between the volume of water and the weight of the giant freshwater prawn head (Macrobrachium rosenbergii de man) so as to increase the protein content in the processed products of sticks. The design used in the research was Completely Randomized Design (RAL) with 1: 1, 1: 2 treatment and without the addition of shrimp head extract (control). The parameters observed were organoleptic test, protein content, and water content. The result of this research showed that the extract of shrimp head with ratio 1: 1 resulted stick protein product 12,67%, while the treatment of prawns extract of prawn with ratio 1: 2 protein content was 13,24% and treatment without giving of shrimp head extract pole protein content only produce stick products with a protein content of 6, 21%. The addition extract of giant freshwater prawn head also yields a preferred flavor of the panelists compared to the treatment without the addition of a giant freshwter prawns head extract.